2010
DOI: 10.1002/mds.23263
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Parkinson's disease among hospital patients with methamphetamine‐use disorders

Abstract: Because methamphetamine exposure to experimental animals can damage brain dopamine neurones, we examined whether hospital patients diagnosed with methamphetamine-related disorders might have greater risk of subsequent admission with a Parkinson's disease diagnosis. This was a population-based cohort study using all statewide inpatient hospital discharge records from July 1, 1990, through June 30, 2000, in California, USA, in which subjects aged at least 50 years were followed for up to 10 years. Individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 48 publications
3
81
1
2
Order By: Relevance
“…Further studies are needed to explore the relationship of the persistent deficits of WM tracts surrounding the basal ganglia and motor function (Caligiuri and Buitenhuys 2005). Two epidemiological studies found prior MA use was a risk factor of later onset Parkinson's disease (Callaghan et al 2010(Callaghan et al , 2012. Some clinical studies using psycho-motor tests observed motor dysfunction in stimulants users (Kalechstein et al 2003;Volkow et al 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to explore the relationship of the persistent deficits of WM tracts surrounding the basal ganglia and motor function (Caligiuri and Buitenhuys 2005). Two epidemiological studies found prior MA use was a risk factor of later onset Parkinson's disease (Callaghan et al 2010(Callaghan et al , 2012. Some clinical studies using psycho-motor tests observed motor dysfunction in stimulants users (Kalechstein et al 2003;Volkow et al 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…2d). Given this potential vulnerability in the SN and that MA abusers may be at greater risk to develop Parkinson's disease (Callaghan et al 2010), it will be important to follow up the incidence of Parkinson's disease in MA addicts who will survive to 62 years of age, the average age of onset of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, several clinical reports have found that patients diagnosed with neurodegenerative diseases, such as PD, had a higher rate of exposure to amphetamine-related drugs at a young age, compared with the general population (Parrott et al, 2004;Callaghan et al, 2010;Christine et al, 2010;Curtin et al, 2015). Since several clinical studies recognize that PD has multiple origins, one hypothesis is that amphetamine-related drugs may be part of the wide array of factors leading to the dopaminergic neuron degeneration that causes the disease (Obeso et al, 2010).…”
Section: Studies In Humansmentioning
confidence: 99%
“…METH is directly neurotoxic to dopaminergic neurons and hence its abuse may increase the risk of developing PD by 2 to 3 fold (Callaghan 2010(Callaghan , 2012Curtin et al, 2015). METH can also result in neurotoxicity to other neurons including serotonergic (Krasnova and Cadet, 2009;Silva et al, 2014), glutamatergic (Simões et al, 2007;Miyazaki et al, 2013;Zhang et al, 2014), GABAergic (Zhang et al, 2006;Mizoguchi and Yamada, 2011;Shen et al, 2013), as well as cholinergic neurons (Lim et al, 2014).…”
Section: Neurotoxicity Of Meth: Selectivity For the Dopaminergic Systemmentioning
confidence: 99%